Populational fluctuation of pest and predator insects in citrus - Chagas, Evandro Ferreira das; Neto, Sinval Silveira; Braz, Antonio Joaquim B. P.; Mateus, César P.B.; Coelho, Iraci Paiva (Pesquisa Agropecuaria Brasileira, 2014)
This study was carried out in a 5.000 m2 area at Piracicaba, SP, Brazil, to determine the behavior of the pest and predator insects in citrus. A portable vacuum collector AS-ESALQ modal as used. Weekly, samples were taken at rondom from the top of ten plants, 20 times per plant. Two species - Aleurothrixus floccosus (Maskell 1896) and Toxoptera citricidus (Kirk 1907) - were the only Coleoptera pests found. They occurred through all the year, having higher frequencies in April and November. The predators from file Coleoptera were: Cycloneda sanguinea (Linné 1763). Nephaspis sp., Scymnus sp, and Stethorus sp. Three species of Neuroptera were found: Chrysopa sp., Megalomus sp., and Hemerobius sp., that have population peaks in January, August and December. One Diptera species was found as of importance: Micrempis sp., which presented four peaks, in the months January, April, August and October.